Kesadaran Kolektif Mahasiswa dan Rakyat Kecil dalam Cerpen Suara dari Jalanan: Kajian Strukturalisme Genetik - Ade Noviyanti; Tatia Sri Ningrum; Cindy Nur Rahma Alini; Didi Supriyadi; Rusli Rusli (Jurnal Bahastra, 2026)
The growing socio-economic inequalities in urban Indonesia have increasingly been reflected in contemporary literary works, positioning literature as a medium for articulating collective social consciousness. This study examines the short story Suara dari Jalanan by Azkiya (2025) through Lucien Goldmann’s genetic structuralism, addressing how collective consciousness and worldview are constructed through the relationship between university students and marginalized communities in the context of economic injustice. Employing a qualitative descriptive method, the analysis focuses on literary text interpretation by examining human facts, collective subjects, meaningful structures, and worldview. The findings reveal that the narrative represents a form of social solidarity emerging as a collective response to rising living costs and structural inequality. The characters Arif and Mbah Marni symbolize a shared consciousness shaped by similar socio-economic experiences despite their differing backgrounds. This study argues that the short story functions not only as a fictional narrative but also as a critical reflection of urban social realities, demonstrating how literature articulates collective resistance and social awareness.